Isolation Of Antimigratory Chemical Constituents From Curcuma Caesia, Curcuma Aeruginosa Rhizomes And Dioscorea Bulbifera Tubers Using Human Breast Cancer Cell Lines - Al-Amin, Md (2021)
Curcuma caesia, Curcuma aeruginosa and Dioscorea bulbifera are used traditionally for the treatment of human ailments including cancer. The present study was carried out to search for antimigratory compounds from C. caesia, C. aeruginosa rhizomes and D. bulbifera tubers using breast cancer cell lines. The chemical constituents from C. caesia and C. aeruginosa rhizomes have been isolated through fractionation. The extracts of C. caesia and C. aeruginosa rhizomes showed concentration-dependent inhibition of MCF-7 and MDA-MB-231 cells. Further study showed that hexane and chloroform fractions of C. caesia rhizomes and chloroform fraction of C. aeruginosa rhizomes are the bioactive fractions that significantly inhibit the viability of breast cancer cells. The chromatographic separation afforded germacrone (1), zerumbone (2), furanodienone (3), curzerenone (4), curcumenol (5), zederone (6), curcumenone (7) and dehydrocurdione (8) from hexane fraction and curcuminol G (9), curcuzederone (10), (1S, 10S), (4S,5S)-germacrone-1(10), 4- diepoxide (11), wenyujinin B (12), alismoxide (13), aerugidiol (14), zedoarolide B (15), zedoalactone B (16) zedoarondiol (17) and isozedoarondiol (18) from chloroform fraction of C. caesia rhizomes. The chromatographic separation afforded germacrone (1), furanodienone (3), curzerenone (4), curcumenol (5) and zederone (6) from chloroform fraction of C. aeruginosa. Cell viability assay of these isolated compounds further revealed that compounds 1-4 and 10, and compounds 1, 3 and 4 are the bioactive compounds of C. caesia and C. aeruginosa, respectively.